2003
DOI: 10.1177/0022002703258197
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Structural Understanding of Coup Risk

Abstract: Although coup risk plays an important role in theories of war, revolution, and democratization, scholars have not developed a rigorous conceptualization and valid measure of the concept. We develop a structural understanding of coup risk as distinct from proximate causes of coups as well as coup-proofing strategies that regimes implement to avert coups. Theoretical insights into factors that predispose regimes toward coup vulnerability provide the groundwork for an improved measure based on strength of civil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
276
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(287 citation statements)
references
References 37 publications
10
276
1
Order By: Relevance
“…Johnson et al (1984) replicated Jackman`s study with wider dataset, ending up to the same conclusion. Civil society impact is also consistent with what Belkin and Schofer (2003) found. They`ve found that civil society is a significant predictor of military coups d`etat.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Johnson et al (1984) replicated Jackman`s study with wider dataset, ending up to the same conclusion. Civil society impact is also consistent with what Belkin and Schofer (2003) found. They`ve found that civil society is a significant predictor of military coups d`etat.…”
Section: Resultssupporting
confidence: 91%
“…Findings are described in the table (1). Results indicate that fragmentation, turnout and civil society are all significant predictors of military coups d`etat in the countries of the South, while there is no empirical evidence that polarization is significant.…”
Section: Resultsmentioning
confidence: 94%
“…First, a large number of scholars argue that a political leader who faces high threats of coups imposed by strong elites is more likely to attempt to diminish the elites' coup-making capabilities. As the likelihood that the military and other elites will attempt a 3 coup increases, the dictator is more inclined to diminish their capabilities to organize a coup by purging strong and competent officers (e.g., Stepan, 1971;Horowitz, 1985;Finer, 1988;Pollack, 1996;Belkin & Schofer, 2003, 2005Pilster & Bohmelt, 2011). In other words, a dictator who faces a high coup risk tends to employ "coup-proofing" strategies in the form of purges and political replacement of military officers and other elites to reduce his coup risk (Biddle & Zirkle, 1996;Quinlivan, 1999;Roessler, 2011).…”
Section: Dictators' Incentive and Opportunity To Weaken Elitesmentioning
confidence: 99%
“…The regime stabilisation effects of economic development on both democracies and autocracies has been attested in various studies (Feng 1997;Belkin and Schofer 2003;Goldstone et al 2010;Maeda 2010). Miller (2012) shows that the probability of violent leader removal decreases significantly when the average income increases.…”
Section: Regime Durability Through Economic Developmentmentioning
confidence: 99%